Evaluation of Hemostatic Compression on Radial Artery Occlusion After Trans Radial Percutaneous Coronary Intervention - Rahman, Atikur; Chowdhury, Tariq Ahmed; Khan, A K S Zahid Mahmud; Afroz, Fahdia; Hoque, Mohammad Faridul; Majumder, Mizanur Rahman; Masum, Mahmudul Hasan; Jahan, Ferdous (Cardiology and Cardiovascular Medicine, 2024)
Background: Radial artery occlusion (RAO) is a significant concern in the trans-radial approach (TRA), limiting future use of the radial artery for procedures such as coronary artery bypass graft surgery (CABG), invasive hemodynamic monitoring, and arterio-venous fistula creation for hemodialysis in chronic kidney disease (CKD) patients through the same vascular approach. This study aimed to evaluate the hemostatic compression on radial artery occlusion after trans-radial percutaneous coronary intervention. Methods: This prospective observational study was conducted in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from September 2018 to August 2019. A total of 140 patients who underwent percutaneous coronary intervention (PCI) through TRA were randomly enrolled and divided into two groups, with 70 cases in each. Group I underwent 2-hour hemostatic compression after trans-radial PCI, while Group II received 6-hour hemostatic compression after the procedure. For data analysis, SPSS version 23.0 was applied. Results: In this study, early radial artery occlusion was observed in 4.3% of patients in group I and 12.8% in group II (P=0.04). Similarly, late radial artery occlusion occurred in 2.8% of patients in group I and 11.4% in group II, with a statistically significant difference (P=0.04). Multivariate logistic regression analysis identified predictors of radial artery occlusion, including a hemostatic compression time of 6 hours (P=0.01), postprocedural nitroglycerine use (P=0.03), and procedure time (P=0.03). Conclusion: A shorter duration of hemostatic compression is associated with a lower incidence of early and late radial artery occlusion after transradial intervention.